2009
DOI: 10.1007/s10856-008-3674-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of highly porous hydroxyapatite from cuttlefish bone

Abstract: Hydroxyapatite structures for tissue engineering applications have been produced by hydrothermal (HT) treatment of aragonite in the form of cuttlefish bone at 200 degrees C. Aragonite (CaCO(3)) monoliths were completely transformed into hydroxyapatite after 48 h of HT treatment. The substitution of CO(3) (2-) groups predominantly into the PO(4) (3-) sites of the Ca(10)(PO(4))(6)(OH)(2) structure was suggested by FT-IR spectroscopy and Rietveld structure refinement. The intensity of the nu(3)PO(4) (3-) bands in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 19 publications
3
58
1
2
Order By: Relevance
“…Despite a porosity exceeding 90% (1), the cuttlebone of some species withstand pressures encountered at up to 500 m in diving depth (2,3). This exceptional combination of high compressive strength, porosity and permeability is extremely desirable for biomimetic and biomedical structural materials, including templates for tissue scaffolds (4,5), hydroxyapatite scaffolds (6)(7)(8), and bone cements (9).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a porosity exceeding 90% (1), the cuttlebone of some species withstand pressures encountered at up to 500 m in diving depth (2,3). This exceptional combination of high compressive strength, porosity and permeability is extremely desirable for biomimetic and biomedical structural materials, including templates for tissue scaffolds (4,5), hydroxyapatite scaffolds (6)(7)(8), and bone cements (9).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of HA using eggshells and phosphoric acid at different mixing ratios (Balazsi et al, 2007) has also been reported. AB-type carbonated nano-powder of HA prepared by hydrothermal transformation of milled oyster shell powders (Lemos et al, 2006) and hydroxyapatite structures for tissue engineering synthesised by hydrothermal treatment of aragonite in the form of cuttlefish bone (Ivankovic et al, 2009 ) are some of the many synthesis methods used for the production of HA from naturally available sources. Jarco et al (1977) was the first to synthesise ultrafine HA powders by chemical reaction between calcium hydroxide and phosphoric acid at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, scientists are searching for alternative bone fillers (Damien and Parsons 1991). Numerous experimental studies have been conducted on cuttlebone (CB) (Rocha et al 2006;Yildirim et al 2007;Ivankovic et al 2009). Due to its aragonite structure, its feasibility as bone graft has been inves-tigated in vitro (Ivankovic et al 2009).…”
mentioning
confidence: 99%
“…Numerous experimental studies have been conducted on cuttlebone (CB) (Rocha et al 2006;Yildirim et al 2007;Ivankovic et al 2009). Due to its aragonite structure, its feasibility as bone graft has been inves-tigated in vitro (Ivankovic et al 2009). It can be obtained easily and inexpensively from all the seas of the world, it is cheap (Rocha et al 2006), it can be shaped easily due to its morphology and mineral composition, it is compatible with other types of bone structure and it has high osteo-inductive capacity (Murugan et al 2006).…”
mentioning
confidence: 99%